Crisis in Turkey: An Analysis of Socio-Political Challenges and Economic Implications - Hanna Audrey (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This scholarly journal article examines the multifaceted crisis currently unfolding in Turkey, encompassing socio-political challenges and their consequential economic implications. The paper delves into the historical context, underlying factors, and recent events that have contributed to the crisis. Additionally, it assesses the potential ramifications on Turkey's domestic stability, regional influence, and global partnerships. By analyzing the crisis through a multidimensional lens, this article aims to provide a comprehensive understanding of the complex situation and its broader implications.